MENGAJARKAN KEBUGARAN JASMANI MELALUI SENAM KEPADA ATLET ATLETIK SMK MUHAMMADIYAH BLIGO - rizqiana, fina; Aditya Tantra, Irfan; Al Fandi, Kurnia; Allam, Faiq; Nuari Panggraita, Gilang (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2023)
The purpose of holding this service is as an experience practice gymnastic skills and help improve the fitness of para athlete. The service team provides solutions by serving the athletes.This is done to provide a gymnastic experience for athletes can do other things that can help improve fitness body. The participants in this dedication were the Bligo Muhammadiyah Vocational High School athletic athletes who were carried out on the school's field, totaling 50 people who took part in this service. This service is carried out by dividing the participants into 5 groups so that each group has 10 people accompanied by 2 trainers who are members of the service. This activity went well, marked by the high enthusiasm of the participants to take part in the activity. This activity also produces good results, which can provide positive benefits for participants.